TAGHYIR WITHIN CHARACTER BUILDING OF THE ISLAMIC TRADITIONAL SCHOOL STUDENTS IN ACEH BESAR - Ikhram, Ikhram; Zulfikar, T.; Muhammad, Mufakhir; Al-Fairusy, Muhajir; Ikhwan, M. (Universitas Islam Negeri Ar-Raniry, 2023)
This study discusses the direction and strategy of developing character education to change the personality and disposition of students towards a more religious, disciplined, and moderate direction, especially those who study at integrated Islamic boarding schools in Aceh Besar using the taghyir approach. This term itself means changes that are made in earnest to shape the personality of students. The study was conducted at four integrated Islamic boarding schools in Aceh Besar; Pesantren Al-Manar, Pesantren Al Falah Abu Lam U, and Pesantren Oemar Diyan. The paradigm of interpretation with a character education approach becomes a framework of thinking in this study. This study uses qualitative research methods, by selecting several informants who are directly involved in the world of education in integrated Islamic boarding schools, to get an emic perspective and observe directly the process of character change carried out. The results of the study show that character building with taghyir methods and models has been practiced by each of the integrated pesantren is almost uniform, considering that the third qibla of pesantren is Gontor which is the basis of the development of modern pesantren in Indonesia. The locus of character change is prioritized on changing attitudes in the context of religion, discipline, respecting differences, and upholding attitudes as a student. Character changes tend to be easily developed among female students, given their attitude of obeying every pesantren regulation. In addition, the example of teachers is the main key in the application of taghyir in the most popular Islamic boarding schools for the formation of the character of students. Taghyir in Pesantren was developed with an emphasis on the value of religious character, and the role of teachers and parents in changing and fostering the character of students to foster the character of students who live in integrated Islamic boarding schools in Aceh Besar.